VR Aquarium, de Diana Domingues: interfaces, interatividade e possibilidades de aproximação - Silveira, Greice Antolini (2010)
This paper portrays Diana Domingues' professional life as well as her artistic working projects which deal with digital technologies, addressing some of the key questions regarding to the artistic domain that includes digital media. In this paper, we try to analyze Domingues' VR Aquarium Project that explores the application of interfaces for immersion in a virtual reality environment. We aim at recognizing and understanding the interface usage in addition to relevant concepts to this field of knowledge; the manner that the artist explores interactivity by visitor's interactive surroundings; and the possible estimates of her work by analyzing how creation occurs, production, deploying, visualization and maintenance.